2011
DOI: 10.1021/jo201809a
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of InCl3with Various Reducing Agents: InCl3–NaBH4-Mediated Reduction of Aromatic and Aliphatic Nitriles to Primary Amines

Abstract: While alternative methods of preparing dichloroindium hydride (HInCl(2)) via the in situ reduction of InCl(3) using lithium amino borohydride (LAB) were explored, generation of HInCl(2) from the reduction of InCl(3) by sodium borohydride (NaBH(4)) was also re-evaluated for comparison. The reductive capability of the InCl(3)/NaBH(4) system was found to be highly dependent on the solvent used. Investigation by (11)B NMR spectroscopic analyses indicated that the reaction of InCl(3) with NaBH(4) in THF generates H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 55 publications
(57 reference statements)
1
45
0
Order By: Relevance
“…32 It was also found that the HInCl 2 produced using the MeLAB/InCl 3 reagent system possesses similar reductive capabilities to that of HInCl 2 prepared via other methods. For example, we were able to reduce aliphatic halides like (3-bromopropyl)benzene to n-propylbenzene in 77% yield (Scheme 29).…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…32 It was also found that the HInCl 2 produced using the MeLAB/InCl 3 reagent system possesses similar reductive capabilities to that of HInCl 2 prepared via other methods. For example, we were able to reduce aliphatic halides like (3-bromopropyl)benzene to n-propylbenzene in 77% yield (Scheme 29).…”
mentioning
confidence: 83%
“…It was discovered that the ratio of InCl 3 to MeLAB played a significant role in the formation of the reducing species (Table 4). 32 When an excess of MeLAB was used (Table 4, entries 1 and 2), the reaction mixture quickly turned dark grey and precipitated colloidal indium metal which aggregated to form a shiny indium nugget. From the weight of the indium metal, it was deduced that indium metal was formed essentially quantitatively in these reactions.…”
Section: Generation Of Hincl 2 Using Lithium Aminoborohydride (Lab)mentioning
confidence: 99%
See 3 more Smart Citations